2014
DOI: 10.3390/molecules19010581
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Mechanisms of Action of Semisynthetic Carnosic Acid Derivatives in Human Cells

Abstract: Carnosic acid (CA) and its semisynthetic derivatives display relevant gastroprotective effects on HCl/ethanol induced gastric lesions in mice. However, little is known on the mechanisms of action of the new compounds. The aim of the present work was to assess the gastroprotective action mechanisms of CA and its derivatives using human cell culture models. A human gastric adenocarcinoma cell line (AGS) and lung fibroblasts (MRC-5) were used to reveal the possible mechanisms involved. The ability of the compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, the potential gastroprotective effect of GE in in vitro studies especially on the gastric human cell line has not yet been fully elucidated. Previous studies have shown that a model of gastric cells impaired by NaT was used to explore the gastroprotective effect of different ingredients against bile-induced injury on the gastric mucosa [10,23]. Hence, in our study the model of AGS damaged by NaT was used to determine the gastroprotective effect of GE in culture model of PUD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the potential gastroprotective effect of GE in in vitro studies especially on the gastric human cell line has not yet been fully elucidated. Previous studies have shown that a model of gastric cells impaired by NaT was used to explore the gastroprotective effect of different ingredients against bile-induced injury on the gastric mucosa [10,23]. Hence, in our study the model of AGS damaged by NaT was used to determine the gastroprotective effect of GE in culture model of PUD.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research done by De Olinda et al reported that Magonia glabrata was demonstrated to protect against gastric lesions caused by indomethacin and ethanol by increasing production of PG [31]. Likewise, results of our study are in agreement with the study of Theoduloz at al., which showed how derivates of the medicinal plant Jatropha isabelii affect increases of PGE2 synthesis after damage with bile salt [10]. It is known that garlic contains fatty acids responsible for increasing level of PG which modulates inflammation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous work, we investigated the gastroprotective activity and cytotoxicity of carnosic acid γ-lactone derivatives [12] as well as carnosic acid derivatives [13] and their gastroprotective mechanisms of action in human cells [14]. In the present report we used click chemistry reactions to prepare new carnosic acid and carnosol derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular mechanisms involved in the effects of carnosic acid include up-regulation of Nuclear factor (erythroid-derived 2)-like 2 (Nfr2) activity [8, 13,55,56], preservation of mitochondrial respiratory function [11,56], mitochondrial depolarization [47], cytochrome-c release [36], increase in Bax:Bcl-2 ratio [36], caspase activation [36,37], up-regulation of NAD + -dependent deacetylase SIRT1 [2], glutathione S-transferase [8,57], death receptor (DR)5 [19], Bcl-2 interacting mediator of cell death (Bim) [19] and p53 up-regulated modulator of apoptosis (PUMA) [19] expression, down-regulation of c-FLIP and Bcl-2 expression [19] as well as stimulation of PGE 2 synthesis [15]. Signaling involved in the effect of carnosic acid further includes phosphatidylinositol 3-kinase (PI3K)/Akt [26,[46][47][48][49], nuclear factor-kappa B (NF-κB) [21,49], and p38 kinase [8, 16,45,57].…”
Section: Introductionmentioning
confidence: 99%